Conservatively managed patients with non-ST-segment elevation acute coronary syndrome are undertreated with indicated medicines. - Elena Candela; Francisco Marín; José Miguel Rivera-Caravaca; Nuria Vicente Ibarra; Luna Carrillo; María Asunción Esteve-Pastor; Teresa Lozano; Manuel Jesús Macías; Vicente Pernias; Miriam Sandín; Esteban Orenes-Piñero; Miriam Quintana-Giner; et al. (PLoS ONE, 2018)
Introduction and aims Patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) are often managed conservatively. Clinical practice guidelines recommend treating these patients with the same pharmacological drugs as those who receive invasive treatment. We analyze the use of new antiplatelet drugs (NADs) and other recommended treatments in people discharged following an NSTE-ACS according to the treatment strategy used, comparing the medium-term prognosis between groups. Methods Prospective observational multicenter registry study in 1717 patients discharged from hospital following an ACS; 1143 patients had experienced an NSTE-ACS. We analyzed groups receiving the following treatment: No cardiac catheterization (NO CATH): n = 134; 11.7%; Cardiac catheterization without revascularization (CATH-NO REVASC): n = 256; 22.4%; percutaneous coronary intervention (PCI): n = 629; 55.0%; and coronary artery bypass graft (CABG): n = 124; 10.8%. We assessed major adverse cardiovascular events (MACE), all-cause mortality, and hemorrhagic complications at one year. Results NO CATH was the oldest, had the most comorbidities, and was at the highest risk for ischemic and hemorrhagic events. Few patients who were not revascularized with PCI received NADs (NO CATH: 3.7%; CATH-NO REVASC: 10.6%; PCI: 43.2%; CABG: 3.2%; p<0.001). Non-revascularized patients also received fewer beta-blockers, angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARB), and statins (p<0.001). At one year, MACE incidence in NO CATH group was three times that of the other groups (30.1%, p<0.001), and all-cause mortality was also much higher (26.3%, p<0.001). There were no significant differences in hemorrhagic events. Belonging to NO CATH group was an independent predictor for MACE at one year in the multivariate analysis (HR 2.72, 95% CI 1.29-5.73; p = 0.008). Conclusions Despite current invasive management of NSTE-ACS, patients not receiving catheterization are at very high risk for under treatment with recommended drugs, including NADs. Their medium-term prognosis is poor, with high mortality. Patients treated with PCI receive better pharmacological management, with high use of NADs.